A combined computational and experimental investigation of the oxidative ring-opening of cyclic ethers by oxoammonium cations. Issue 16 (31st March 2016) - Loman, Jacob. J.; Carnaghan, Emma R.; Hamlin, Trevor A.; Ovian, John M.; Kelly, Christopher B.; Mercadante, Michael A.; Leadbeater, Nicholas E.
Abstract : The oxidative ring-opening of cyclic ethers using oxoammonium cations is investigated using experimental and computational methods. Abstract : The propensity of oxoammonium cations to facilitate the oxidative ring-opening of cyclic ethers to their corresponding distal hydroxy ketones is investigated. The reaction has been evaluated using experimental and computational methods to gain deeper insight into trends in reactivity.